2017
DOI: 10.1186/s12885-017-3493-0
|View full text |Cite
|
Sign up to set email alerts
|

Complete surgical resection improves outcome in INRG high-risk patients with localized neuroblastoma older than 18 months

Abstract: BackgroundAlthough several studies have been conducted on the role of surgery in localized neuroblastoma, the impact of surgical timing and extent of primary tumor resection on outcome in high-risk patients remains controversial.MethodsPatients from the German neuroblastoma trial NB97 with localized neuroblastoma INSS stage 1–3 age > 18 months were included for retrospective analysis. Imaging reports were reviewed by two independent physicians for Image Defined Risk Factors (IDRF). Operation notes and correspo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
38
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 64 publications
(39 citation statements)
references
References 22 publications
0
38
0
1
Order By: Relevance
“…Achieving GTR has been reported to improve outcomes in some studies of high‐risk neuroblastoma and is influenced by several factors including the site and extent of primary disease, patient comorbidities, and surgical expertise . In the NB97 trial, GTR did not improve OS or local control; however, in the same study, some patients with STR received 36 Gy RT to the tumor bed, whereas none of the GTR patients received RT.…”
Section: Discussionmentioning
confidence: 99%
“…Achieving GTR has been reported to improve outcomes in some studies of high‐risk neuroblastoma and is influenced by several factors including the site and extent of primary disease, patient comorbidities, and surgical expertise . In the NB97 trial, GTR did not improve OS or local control; however, in the same study, some patients with STR received 36 Gy RT to the tumor bed, whereas none of the GTR patients received RT.…”
Section: Discussionmentioning
confidence: 99%
“…Similar results were reported from a German study, which showed that the extent of best operation had no impact on EFS [ 11 ]. In patients older than 18 months old with localized HRNBL, however, patients who underwent complete resection had superior local-progression-free survival (LPFS), EFS, and OS compared with patients who had gross total resections, incomplete surgery, or biopsy only [ 12 ]. Thus, in patients with metastatic high-risk disease, surgical morbidity should be carefully considered when planning resection and should not occur at the expense of a complete resection.…”
Section: Treatmentmentioning
confidence: 99%
“…Over 75% of patients are categorized as high-risk with a poor overall 5-year survival of less than 50%, despite intensive treatment with high-dose chemotherapy followed by surgery, autologous stem cell transplantation, radiotherapy and immunotherapy 2 , 3 . Resection of high-risk NB is associated with a risk for serious surgical complications, since the tumor often encases major blood vessels leading to severe hemorrhage and/or unplanned organ damage 4 , 5 . Discriminating cancerous tissue from healthy tissue is challenging, but of great importance to achieve optimal tumor resection, while preserving healthy tissue, which can thereby increase survival 6 , 7 .…”
Section: Introductionmentioning
confidence: 99%